Seasonal and Interannual Variations of Surface Nutrients and Hydrography in the Norwegian Sea - Ibrahim, Ahmed Saif Aldein Alsaid (The University of Bergen, 2012)
Seasonal and interannual variations of surface nutrients and hydrography data obtained in period (1997-2010) by the Institute of Marine Research over three transects: Fugløya-Bjørnøya, Gimsøy and Svinøy located in the Norwegian Sea have been studied. The results over the Fugløya-Bjørnøya transect show good signature of the seasonal cycle of nitrate and temperature reflecting both bloom and post-bloom periods. The Gimsøy transect shows a weak seasonal cycle of nitrate and temperature in the outer part because there is no enough data during the bloom and post-bloom period. But the middle and inner part show good seasonal cycle of nitrate and temperature during the two periods. Finally, the Svinøy transect shows good seasonal cycle of nitrate and temperature during the bloom and post-bloom. The results over the three transects do not reveal much information on the interannual variations of temperature, salinity and nitrate. This due to the changes in the timing of the cruise. Also the availability of information is short over three transects. Master i Meteorologi og oseanografi MAMN-GEOF GEOF399